Controversies in the treatment of prostate cancer - Moser, Lutz 1968-; Schostak, Martin 1965-; Miller, Kurt; Hinkelbein, Wolfgang 1948- (Frontiers of radiation therapy and oncology, 2008)
Treatment strategies in prostate cancer underlie a permanent change due to continuous improvements. Based on the 10th International Symposium on Special Aspects of Radiotherapy held in Berlin in 2006, this volume highlights key advances in surgical, radiooncological and systemic treatment standards for prostate cancer. Furthermore, interdisciplinary co-operations and controversies are presented and future developments are discussed. The four parts of the book cover the different stages of the disease - localized prostate cancer, the lymph node positive situation, biochemical recurrence, and hormone-refractory and metastatic prostate cancer. Special attention is given to the value and sequence of systemic treatment options in relation to surgery and radiotherapy.Proving the reader with the latest treatment standards of prostate cancer, this book will be of great value to urologists and radiation oncologists as well as to all others involved in the care of patients with prostate cancer